2007
DOI: 10.1124/jpet.107.120675
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and Ethanol Activate Protein Kinase A Synergistically via Giβγ Subunits in Nucleus Accumbens/Ventral Tegmental Cocultures: The Role of Dopamine D1/D2and Adenosine A2AReceptors

Abstract: Tobacco and alcohol are the most commonly used drugs of abuse and show the most serious comorbidity. The mesolimbic dopamine system contributes significantly to nicotine and ethanol reinforcement, but the underlying cellular signaling mechanisms are poorly understood. Nicotinic acetylcholine (nACh) receptors are highly expressed on ventral tegmental area (VTA) dopamine neurons, with relatively low expression in nucleus accumbens (NAcb) neurons. Because dopamine receptors D 1 and D 2 are highly expressed on NAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
(67 reference statements)
1
11
0
2
Order By: Relevance
“…We also found that the increase in NAshell firing with apomorphine + MCH was inhibited by antagonists of either DA1, DA2, or MCH receptors or by an agent that blocks both DA1 and DA2 receptors. These results concur with our previous findings that DA1 and DA2 receptors interact to enhance NAshell activity (Hopf et al, 2003; Hopf et al, 2005; Chung et al, 2009) (see also Seif et al, 2011 in the NAcb core and Inoue et al, 2007), and suggest that apomorphine enhancement of firing required both DA1 and DA2 receptors in addition to an interaction with MCH receptors. The apomorphine + MCH increase in firing was prevented by a PKA inhibitor, consistent with previous work showing that PKA is an important mediator of NAcb dopaminergic signaling involving DA1 receptors (Svenningsson et al, 2004), including dopamine receptor enhancement of NAshell firing (Hopf et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the increase in NAshell firing with apomorphine + MCH was inhibited by antagonists of either DA1, DA2, or MCH receptors or by an agent that blocks both DA1 and DA2 receptors. These results concur with our previous findings that DA1 and DA2 receptors interact to enhance NAshell activity (Hopf et al, 2003; Hopf et al, 2005; Chung et al, 2009) (see also Seif et al, 2011 in the NAcb core and Inoue et al, 2007), and suggest that apomorphine enhancement of firing required both DA1 and DA2 receptors in addition to an interaction with MCH receptors. The apomorphine + MCH increase in firing was prevented by a PKA inhibitor, consistent with previous work showing that PKA is an important mediator of NAcb dopaminergic signaling involving DA1 receptors (Svenningsson et al, 2004), including dopamine receptor enhancement of NAshell firing (Hopf et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Although gene deletion and pharmacological studies have implicated both D 1 and D 2 receptors in mediating dopaminergic responses to EtOH administration (El-Ghundi et al, 1998;Phillips et al, 1998;Eiler et al, 2003;Inoue et al, 2007), the D 1 subtype appears to be particularly important with respect to the rewarding properties of EtOH and motivation for its consumption. For instance, administration of the D 1 receptor antagonists SCH23390 or ecopipam decreases EtOH consumption in mice, whereas administration of the D 1 agonist SKF81297 with EtOH facilitates alcohol-related behaviors (El-Ghundi et al, 1998;D'Souza et al, 2003;Price and Middaugh, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The key effector protein, downstream of D1 receptors and inhibited by D2 receptor activation, is protein kinase A (PKA) [108,121,122]. Activation of PKA phosphorylates dopamine-and cyclic AMP-regulated phosphoprotein of 32kDa (DARPP-32) at Thr34, making it a potent inhibitor of protein phosphatase 1.…”
mentioning
confidence: 99%